Bacteria-Plant interactions: an added value of microbial inoculation - Ogata-Gutiérrez, Katty (2020)
High world population and the increase in global food demands results in an indiscriminate use of chemical fertilizers by farmers, causing soil deterioration and other environmental problems. In recent years there has been a collective concern to preserve the environment through sustainable and environmentally friendly techniques. Plant growth-promoting bacteria (PGPB) are widely known to benefit plants in a sustainable manner, reducing chemical fertilizers application. Many studies have shown that these bacteria not only improve crop yields but also its quality, increasing certain nutrients and molecules that are important for human health such as aminoacids, proteins, vitamins, flavonoids, antioxidants, essential oils, among others. This work compiles recent information of PGPB as an alternative of chemical fertilizer for improving crop yields and plant metabolites production.